Professional Identity Construction Of Junior Secondary Efl Teacher In Indonesian Islamic Boarding Schools - Ameliya Tus Soleha; Bradhiansyah Tri suryanto (CV Putra Publisher, 2026)
This study aimed to explore the lived experiences of junior secondary EFL teachers constructing their professional within Islamic boarding school (pesantren) settings in Indonesia. A qualitative phenomenological design was employed following (Moustakas, 1994) transcendental phenomenological procedures. Four certified junior secondary EFL teachers at Nurul Jadid Islamic boarding school were selected through purposive sampling. Data were collected via semi-structured interview, classroom observation, and document analysis. Four themes emerged: (1) Professional Identity as a moral and educational calling (Amanah); (2) Identity development accumulated teaching experiences; (3) negotiating of dual roles as EFL teacher and religious educator (ustad); and (4) the constitutive influence of pesantren culture and professional development on identity construction. Findings are contextually bounded to two institutions with four participants. Future studies should involve multiple Pesantren contexts and longitudinal design.